Branching Out in Roots: Uncovering Form, Function, and Regulation. Issue 2 (18th August 2014) - Atkinson, Jonathan A.; Rasmussen, Amanda; Traini, Richard; Voß, Ute; Sturrock, Craig; Mooney, Sacha J.; Wells, Darren M.; Bennett, Malcolm J.
Abstract : The diversity of postembryonic root forms and their functions add to our understanding of the genes, signals and mechanisms regulating lateral and adventitious root branching in the plant models Arabidopsis and rice . Abstract: Root branching is critical for plants to secure anchorage and ensure the supply of water, minerals, and nutrients. To date, research on root branching has focused on lateral root development in young seedlings. However, many other programs of postembryonic root organogenesis exist in angiosperms. In cereal crops, the majority of the mature root system is composed of several classes of adventitious roots that include crown roots and brace roots. In this Update, we initially describe the diversity of postembryonic root forms. Next, we review recent advances in our understanding of the genes, signals, and mechanisms regulating lateral root and adventitious root branching in the plant models Arabidopsis ( Arabidopsis thaliana ), maize ( Zea mays ), and rice ( Oryza sativa ). While many common signals, regulatory components, and mechanisms have been identified that control the initiation, morphogenesis, and emergence of new lateral and adventitious root organs, much more remains to be done. We conclude by discussing the challenges and opportunities facing root branching research.